Presidential Threshold Between the Threshold of Candidacy and Threshold of Electability - Suparto Suparto (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2018)
Abstract. In judicial review on Article 9 of Law Number 42 of 2008 on The Election of President and Vice-President which regulates Presidential threshold, the Constitutional Court refused on the grounds that it is an open legal policy which mandated by Article 6 paragraph (5) of the 1945 Constitution that the administration of the election of President and Vice-President will be further regulated in a Law. This reasoning is insufficient because Article 6 paragraph (5) regulates procedures (phases of the process), not requirements for candidates of President and Vice President to be eligible on participating in the election. Moreover Article 9 of Law Number 42 of 2008 has the potential to expand the norms as stipulated in Article 6A paragraph (2) of the 1945 Constitution that the candidates for President and Vice President shall be nominated by a political party or coalition of political parties participating in the election before the election without any other frills (the threshold). Keywords: Presidential Election, Presidential Threshold Abstrak. Dalam pengujian Pasal 9 Undang-Undang Nomor 42 Tahun 2008 tentang Pemilihan Umum Presiden dan Wakil Presiden mengatur tentang Presidential threshold. Mahkamah Konstitusi menolak dengan alasan hal tersebut merupakan open legal policy dengan bersandarkan pada Pasal 6 ayat (5) Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 bahwa tata laksana pelaksanaan pemilihan Presiden dan Wakil Presiden lebih lanjut diatur dalam Undang-Undang. Argumentasi tersebut kurang tepat karena Pasal 6 ayat (5) mengatur tata laksananya (proses tahapan pelaksanaan) bukan persyaratan bagi pasangan calon Presiden dan Wakil Presiden untuk menjadi peserta pemilu. Selain itu, Pasal 9 Undang-Undang Nomor 42 Tahun 2008 tersebut berpotensi memperluas norma sebagaimana yang diatur dalam Pasal 6A ayat (2) Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 bahwa pasangan calon Presiden dan Wakil Presiden diusulkan oleh partai politik atau gabungan partai politik peserta pemilu sebelum pemilu tanpa adanya embel-embel lain (adanya ambang batas).Kata kunci: Pemilu Presiden, Presidential Threshold.